Adoptive T-cell immunotherapy from third-party donors: characterization of donors and set up of a T-cell donor registry - Eiz-Vesper, Britta; Maecker-Kolhoff, Britta; Blasczyk, Rainer (Frontiers in Immunology, 2013)
Infection with and reactivation of human cytomegalovirus (CMV), Epstein-Barr virus (EBV), and adenovirus (ADV) are frequent and severe complications in immunocompromised recipients after hematopoietic stem cell transplantation (HSCT) or solid organ transplantation (SOT). These serious adverse events are associated with significant morbidity and mortality. Donor lymphocyte infusions (DLIs) are often used to treat both viral infections and leukemia relapses after transplantation but are associated with potentially life-threatening graft-versus-host disease (GvHD). Adoptive immunotherapy with virus-specific cytotoxic effector T cells (CTLs) derived from seropositive donors can rapidly reconstitute antiviral immunity after HSCT and organ transplantation. Therefore, it can effectively prevent the clinical manifestation of these viruses with no significant acute toxicity or increased risk of GvHD. In conditions, where patients receiving an allogeneic cord blood transplant or a transplant from a virus-seronegative donor and since donor blood is generally not available for solid organ recipients, allogeneic third party T-cell donors would offer an alternative option. Recent studies showed that during granulocyte colony-stimulating factor (G-CSF) mobilization, the functional activity of antiviral memory T cells is impaired for a long period. This finding suggests that even stem cell donors may not be the best source of T cells. Under these circumstances, partially human leukocyte antigen (HLA)-matched virus-specific CTLs from healthy seropositive individuals may be a promising option. Therefore frequency assessments of virus-specific memory T cells in HLA-typed healthy donors as well as in HSCT/SOT donors using a high throughput T-cell assay were performed over a period of 4 years at Hannover Medical School. This chapter will address the relevance and potential of a third-party T-cell donor registry and will discuss its clinical implication for adoptive T-cell immunotherapy